PWE-403 Impact of the lorec programme on low rectal cancer surgery in a uk hospital. (22nd June 2015) - Blong, J; Chhabra, A; James, K; Arumagam, P; Feldman, M
Abstract : Introduction: The higher rates of rectal perforation and positive resection margins (CRM) associated with abdominoperineal excision of the rectum (AP), compared with low anterior resection (LAR), are believed to explain the higher rates of local recurrence seen with AP. This has led to renewed emphasis on cylindrical excision of the anorectum with the levator muscles en-bloc, and in the UK the Low Rectal Cancer development programme (LOREC) has been established to improve decision making and surgical technique. Our Trust was among the first to participate in LOREC early in 2011 and from that point just 2 surgeons performed prone extralevator AP (ELAPE). This paper reports our first four years' ELAPE experience and compares outcomes with our previous audit and international results. Method: Patients with adenocarcinoma <2 cm above the anorectal junction or with tumour breaching the levators on MRI are considered unsuitable for sphincter saving surgery and so undergo ELAPE. Where there is doubt, examination under anaesthetic is used to determine whether LAR can be performed. Patients with threatened CRM have long course chemoradiotherapy (LCRT) and reconstruction with a rectus abdominus flap; others have Permacol reconstruction. ELAPE is also used for residual or recurrent squamous cell carcinoma after chemoradiotherapy. Demographics, surgical and histological details were collected from our prospective database with retrospective review of radiology and correspondence to identify complications and recurrence. The primary outcome was intraoperative tumour perforation or CRM <1 mm. Secondary outcomes were pelvic recurrence within 2 years and perineal complications. Results: 2003–2009 9 surgeons performed AP for 95 patients with 12% positive CRM or intraoperative rectal perforation and 14% local recurrence. Since February 2011 48 patients have undergone ELAPE (32M:16F), median age 66 years (range 37–88) with median follow-up 23 months (3–46 months). 28 patients had LCRT. One patient had a perforated tumour preoperatively and 2 had CRM <1 mm with no intraoperative rectal perforations (total 6%). There were no deaths within 30 days of surgery, 1 death within 90 days. Of the 26 patients with >24 months follow up there has been 1 local recurrence (4%), none in the patients with shorter follow up. 12% had prolonged perineal wound healing, 4% had perineal hernia. Conclusion: Our results demonstrate safe adoption of the modified technique with good outcomes, compared to previously published local recurrence rates of 10–30%. Closing the perineal wound either with VRAM flap in post neoadjuvant patients, or Permacol mesh repair, gives a low incidence of perineal wound complications. LOREC has enabled safe rapid spread of the ELAPE technique with an improvement in outcomes. Disclosure of interest: None Declared.